Performance of Indian Agriculture A Districtwise Study - Planning Commission (Planning Commission, 1979)
The post-independence period has marked a turning point in the history of agricultural development in India. It has been estimated that total agricultural output increased at the paltry rate of about .8 per cent per annum during the first half of the 20th century and that foodgrains output remained stagnant during this period. Compared with this, bath total agricultural output and foodgrains output recorded an annual growth rate of about 2.6 per cent during the post-independence third quarter of the century.
Planning Commission Government of India
Planning Commission Government of India